Impact of Financial Performance on Stock Price Volatility: A Case of Nepalese Microfinance Companies - Madai, Tek Bahadur (KIC International Journal of Social Science and Management, 2023)
With the explanatory variables of ROE, ROA, D/P ratio, P/E ratio, and BVPS, this study investigates the impact of financial performance on the stock price instability of microfinance companies listed on the Nepal Stock Exchange (NEPSE). The age and size of microfinance companies have been used as control variables. It has also observed the investor’s behavior toward these variables. The study follows a quantitative approach with descriptive, causal-comparative, and survey research design. Multiple regression analysis is used to examine the causal relation between stock price volatility and the profitability of microfinance companies. This study has analyzed the annual report of 31 microfinance companies with 183 observations and 121 responses to a questionnaire received from the investors. According to this study, microfinance organizations’ capacity to produce profits has a considerable impact on share price volatility. The survey result of the study reveals that the investors of microfinance companies are more sensible towards earning ability and past performance of the companies. The results of this investigation may be beneficial to the investors of microfinance companies to select the companies for investment. Acknowledging the limitation of data used in this study, further study can be conducted by taking other industries like banking, insurance, hotel, and manufacturing companies listed in the NEPSE. Besides this, a behavioral study about investors’ responses toward market factors can be conducted by taking a large sample of investors.